Medieval art and architecture (Boulder, Colo. Alarion Press, 1985)
Covers the period from the fall of Rome through the sixteenth century, highlighting European history and developments through the art and architectural achievements of each period.
VHS format.
Alarion Press, Inc.; author, Ann Campbell.
Originally issued as filmstrip in 1984.
[v.1] Early medieval art and architecture - [v.2] Late medieval art and architecture - [v.3] Visual glossary.
Keywords: Art, Medieval -- Study and teaching (Secondary).; Architecture, Medieval -- Study and teaching (Secondary).; Middle Ages